Mortality Audit In COVID-19 Cases of the Omicron Variant in Persahabatan Hospital - Susanto, Agus Dwi; Djasri , Hanevi (Respiratory Science, 2025)
Background: SARS-CoV-2, the virus that causes COVID-19, has mutated into various variants. Deaths in COVID-19 cases caused by the Omicron variant had the highest rate compared to other variants.  This research aims to mortality audit of the Omicron variant of COVID-19 in 2022 at Persahabatan Hospital. Method: This is a cross-sectional observational study focusing on the death audit form recommended by the official Indonesian Hospital Association. Used data from Medical Cause of Death Certificate (SMPK) and medical records of patients treated and died at Persahabatan Hospital in January-December 2022. The causes of death (COD) from the audit results were compared with SMPK. Conducted interviews with the doctor who takes care of patients to explore the root of the problem and improvement efforts. Results: Of the 568 COVID-19 patients with the Omicron variant hospitalized, 130/568 died. As many as 42.52% of the COVID-19 variant Omicron patients died from COVID-19 and 57.48% had COVID-19. The three most COD were respiratory failure, MOF and septic shock. The three underlying COD were COVID-19, bacterial pneumonia and lung cancer. The COD in SMPK and the results of the mortality audit are only appropriate for 23.62%. The best three suggestions for improving clinical management are evaluating the patient supervision/monitoring system, testing for COVID-19 antigens carried out earlier before PCR, and providing special services for COVID-19 patients with comorbid. The top three suggestions for improving hospital managerial aspects are to create and evaluate a special SOP for COVID-19 patients with comorbid, add special service facilities for COVID-19 patients with comorbid and increase ICU bed capacity and human resources. Conclusion: The COVID-19 variant Omicron patients died due to COVID-19 and had COVID-19. The three most COD were respiratory failure, MOF and septic shock. Only 23.62% of COD from SMPK were consistent with the results of the mortality audit.